Aging, Cell Senescence, the Pathogenesis and Targeted Therapies of Osteoarthritis - Zhang, Xin-Xin; He, Shi-Hao; Liang, Xu; Li, Wei; Li, Tian-Fang; Li, Dai-Feng (Frontiers in Pharmacology, 2021)
Osteoarthritis (OA) is a chronic, debilitating joint disease characterized by progressive destruction of articular cartilage. For a long time, OA has been considered as a degenerative disease, while recent observations indicate the mechanisms responsible for the pathogenesis of OA are multifaceted. Aging is a key factor in its development. Current treatments are palliative and no disease modifying anti-osteoarthritis drugs (DMOADs) are available. In addition to articular cartilage degradation, cellular senescence, synovial inflammation and epigenetic alterations may all have a role in its formation. Accumulating data demonstrate a clear relationship between the senescence of articular chondrocytes and OA formation and progression. Inhibition of cell senescence may help identify new agents with the properties of DMOADs. Several anti-cellular senescence strategies have been proposed and these include sirtuin-activating compounds (STACs), senolytics and senomorphics drugs. These agents may selectively remove senescent cells or ameliorate their harmful effects. The results from preclinical experiments and clinical trials are inspiring. However, more studies are warranted to confirm their efficacy, safety profiles and adverse effects of these agents.